(untitled) (Palíndromo, 2023)
This visual article presents the experience of publishing the book “Imminence” and focuses on its poetic, material, and conceptual aspects, as well as the relationship with the photographed contexts and the presence of the definition of ruin. The aim is to observe, establish, and create traces through the creation of artist publications.